Gudea's temple building : the representation of an early Mesopotamian ruler in text and image - Suter, Claudia E. (Groningen : : Styx, 2000)
Gudea of Lagash, who ruled at the end of the third millennium B.C., wanted to be remembered as a temple builder. An extensive narrative inscribed on two huge clay cylinders, one of the longest and best preserved Sumerian texts, recounts his construction of the temple of Ningirsu, Lagash's patron deity. More than sixty sculpted limestone fragments belong to several "stelae" erected in the temples Gudea built and depict their construction. A large number of inscribed and often sculpted, artifacts provide additional information on Gudea's activities. This study treats this visual and textual material as a coherent corpus for the first time. It analyses contents, narrative structure, composition and message. Text and image are compared to elucidate the characteristics of each medium and to arrive at a comprehensive picture of the royal rhetoric of the time. The book includes a catalogue of all artifacts, and a translation of selected text passages.
Three folded leaves of plates in pocket attached to inside back cover.
Includes bibliographical references and index.